PENDAMPINGAN BUDIDAYA SAYURAN ORGANIK DI DESA NGIDIHO KECAMATAN GALELA BARAT - Kastanja, Ariance; Patty, Zeth; Hi. Syawal, Askia; Natalia Malieser, Desrita (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Organic vegetables are one of the food products that have many benefits for the human body such as vitamins, minerals, and fiber that are beneficial in the body's metabolic processes. Vegetable Cultivation Assistance is one of the activities of the KKN Student of Hein Namotemo University, which is carried out for the PKK group. assistance as well as a solution for the provision of vegetables for household needs. This service activity aims to increase the knowledge and skills of PKK Ngidiho members in the practice of organic vegetable cultivation while being able to meet the nutritional needs of the family. The method used in this service activity is counseling and making organic vegetable plantations. The results of this activity indicate that the increasing knowledge and skills of the PKK team in organic vegetable cultivation.